Relationship between presenting symptoms and tumor location in colorectal cancer patients - Fitri Dewi Ismida; Desi Maghfirah; Nurbahri L Salam; Fauzi Yusuf; Vera Dewi Mulia; Avisena Gatot Purnomo (Universa Medicina)
Background Colorectal cancer (CRC) often shows symptoms at an advanced stage, causing delayed diagnosis and poorer prognosis. Initial symptoms, or chief complaints, are usually identified through patient history and can vary based on tumor location. This can help in establishing a diagnosis. This study aimed to determine the relationship between presenting symptoms and tumor location in CRC patients at Zainoel Abidin Regional General Hospital, Banda Aceh.